2017
DOI: 10.1089/acu.2017.1237
|View full text |Cite
|
Sign up to set email alerts
|

Does Ear Acupuncture Have a Role for Pain Relief in the Emergency Setting? A Systematic Review and Meta-Analysis

Abstract: Objective: Ear acupuncture might be the form of acupuncture best suited to improving acute pain management in the emergency department (ED). The primary aim of this review was to assess the analgesic efficacy of ear acupuncture in the ED. Secondary outcomes included measures of patient satisfaction, adverse effects, cost, administration techniques, and reduction of medication usage. Methods: Seven databases and Google Scholar were searched up to April 27, 2017, using MeSH descriptors for three overarching them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(80 citation statements)
references
References 46 publications
3
73
1
1
Order By: Relevance
“…Anecdotally, clinical documentation indicated that the veterans: ''Feel much better with BFA'' and ''Is even going off methadone and has better mental clarity.'' Overall, the numbers of the Fargo VA population were similar to larger populations in previous studies 7,8,[12][13][14][15][16][17][18][19][20] with a significant average decrease of 1.3 points on the 0-10 NRS (P < 0.01). See Table 2.…”
Section: Nrs and Bfa Treatmentsupporting
confidence: 83%
See 3 more Smart Citations
“…Anecdotally, clinical documentation indicated that the veterans: ''Feel much better with BFA'' and ''Is even going off methadone and has better mental clarity.'' Overall, the numbers of the Fargo VA population were similar to larger populations in previous studies 7,8,[12][13][14][15][16][17][18][19][20] with a significant average decrease of 1.3 points on the 0-10 NRS (P < 0.01). See Table 2.…”
Section: Nrs and Bfa Treatmentsupporting
confidence: 83%
“…The first meta-analysis on BFA-either as a stand-alone treatment or coordinated with other methods in an ER setting-was performed by the United Air Force Acupuncture and Integrative Medicine Center in 2017. 12 The researchers there analyzed 6 randomized controlled trials (RCTs) 7,13-17 and 2 observational studies 18,19 and found significant results in decreased post treatment pain in all reviewed articles by an average of 2.5 points on a numeric rating scale (NRS) with no significant adverse effects and overall improved patient satisfaction.…”
Section: Bfa Effectiveness For Pain Interventionmentioning
confidence: 99%
See 2 more Smart Citations
“…E ar acupuncture has been shown to be effective in pain-score reduction for acute and chronic pain in a variety of comparator groups and settings. 1,2 Battlefield Acupuncture (BFA), a subset of auricular acupuncture developed by Richard C. Niemtzow, MD, PhD, MPH, has been promoted by a project called the Acupuncture Across Clinical Settings (ATACS) program, and has led to widespread promulgation of this simple 5-point auricular technique used to treat both acute and chronic pain. 3,4 It has been anticipated that the number of patients undergoing BFA will increase markedly over the upcoming years.…”
Section: Introductionmentioning
confidence: 99%